Teaching social studies through teaching thinking and its impact on the achievement of classroom students The second intermediate and develop their thinking - Dr. Riyad Nouri Muhammad Mardan (Journal of College of Education, 2023)
The current research aims to develop thinking and raise the level of achievement for second-year middle school students. The researcher followed the experimental method that relied on a quasi-experimental design. The sample consisted of 57 students, divided into two groups, the experimental group (31 students), and the control group (26 students). The research materials and tools consist of a teacher’s guide and an opinion poll for middle school social studies teachers to determine the eight most important thinking skills appropriate for teaching social studies to second middle school students, an achievement test, and a thinking test. The data was processed using the Statistical Package for the Social Sciences (SPSS) using a test for linked groups and groups. Unrelated, and the effect size was calculated using the ETA squared in the experimental and control groups in favor of the experimental group There are also statistically significant differences between the average scores of the experimental group students in the pre- and post-application in favor of the post-application. The study showed the effectiveness of teaching thinking through the curriculum in developing thinking and raising the level of achievement.
Keywords: teaching , social studies , teaching thinking , achievement , developing thinking